Features of the work of small innovative enterprises on the basis of military institutions - V. V. Pekhterev (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2021)
The importance of this article need to develop a new approach to small business management. The emergence of new business practices requires a review of existing business management systems or the acquisition of new unique management skills. This article highlights the key differences between small industry and humanity and highlights the key aspects of work that should be considered when working with a small military planning organization. At the end of this work, decisions were made on the priorities in the life of the management of small capable companies, which will contribute to the formation of the management idea of such organizations. The paper shows that in the current economic crisis, the success of small businesses is largely due to the effectiveness of their new development system and the success of the new system in which they operate. Development and implementation by entrepreneurs and scientists of investment projects in the field of science, of production processes in small enterprises, to obtain greater opportunities for competition in international and international markets. The author considers the priorities of opening a small business, points out the problems that small businesses face during transformation, and indicates the best ways to solve emergency situations in the economic sector. The following is the share of organizations engaged in small innovative activities and their profitability over the past ten years. The author reflected the effectiveness of the creation of small innovative enterprises, forming the features of their work, displaying feedback and sources of innovative solutions. As a result, based on the survey data, I concluded that there is a positive trend in the growth of small innovative enterprises based on military institutions.